Wnt Signaling Activates Shh Signaling in Early Postnatal Intervertebral Discs, and Re-Activates Shh Signaling in Old Discs in the Mouse - Winkler, Tamara (Public Library of Science, 2014)
Intervertebral discs (IVDs) are strong fibrocartilaginous joints that connect adjacent vertebrae of the spine. As discs age they become prone to failure, with neurological consequences that are often severe. Surgical repair of discs treats the result of the disease, which affects as many as one in seven people, rather than its cause. An ideal solution would be to repair degenerating discs using the mechanisms of their normal differentiation. However, these mechanisms are poorly understood. Using the mouse as a model, we previously showed that Shh signaling produced by nucleus pulposus cells activates the expression of differentiation markers, and cell proliferation, in the postnatal IVD. In the present study, we show that canonical Wnt signaling is required for the expression of Shh signaling targets in the IVD. We also show that Shh and canonical Wnt signaling pathways are down-regulated in adult IVDs. Furthermore, this down-regulation is reversible, since re-activation of the Wnt or Shh pathways in older discs can re-activate molecular markers of the IVD that are lost with age. These data suggest that biological treatments targeting Wnt and Shh signaling pathways may be feasible as a therapeutic for degenerative disc disease.